Logistics in Tourism: The Challenges and Development Prospects in the Modern World - Prochan Anna O. (Bìznes Inform, 2023)
Logistics in tourism is one of the most important components of the tourism industry, ensuring the efficient organization and coordination of tourism services. Recently, with the development of technology and changes in demand, the importance of improving logistics processes in tourism has been growing. The purpose of the study is to identify the challenges and prospects for the development of logistics in tourism in the modern world. The methodological basis of the study was the analysis of scientific literature, statistical data and own experience in the field of tourism and logistics. To achieve the goal of the study, the challenges and prospects for the development of logistics in tourism were analyzed based on the study of literature and statistics for recent years. The results of the study showed that tourism logistics faces significant challenges in the modern world. One of the most important is the rapid change in the needs and requirements of tourists, which requires equally rapid adaptation and improvement of logistics processes. Another important challenge is the growing competition and the increasing number of players in the tourism market, which requires reducing logistics costs and increasing the efficiency of logistics processes. This is one of the prospects for further development of the industry – with the development of technology and the use of innovative solutions, it is possible to reduce the cost of logistics services and improve their quality. In addition, with the proliferation of electronic platforms and the growing number of tourists using online services to book and purchase services, there is a need to develop electronic logistics in tourism. This involves the automation of business processes, which reduces the risk of human error and increases the efficiency of interaction between participants in the supply chain. The novelty of the study lies in the fact that the work is devoted to a topical issue that is rather poorly studied in Ukrainian science. The author analyzes the current state of logistics in tourism and describes the challenges facing this industry due to the growth of tourist traffic and the development of technology. It is justified that logistics is extremely important for the development of tourism, as it ensures the efficient organization and coordination of tourism services. However, at the same time, there is a growing number of challenges associated with the growth of tourism intensity and the increase in tourist flows, the development of technology and the competitive environment.